Cycling towards sustainability: The transformative potential of urban design thinking in a sustainable living lab. - Alexandrakis, Julian (Elsevier, 2021)
The recent proliferation of Sustainable Living Labs as experimental arenas within and through which contemporary cities try to tackle today’s sustainability challenges, has led to a systematic integration of user’s consideration in the design and testing of Sustainable Product‐Service Systems (S.PSSs). Therefore, it is crucial to co‐create with users throughout the whole innovation process of Sustainable Living Labs and to discover userneeds and shape S.PSSs according to how theyfit into users’daily life. Yet, it remains understudied how thecocreation knowledge in a multi‐stakeholder environment of a Sustainable Living Lab can be facilitatedmethodically to fully utilize the transformative potential and to accelerate sustainability transition in line withthe SDGs. Hence, this paper focuses on the integration of the co‐creation method of Urban Design Thinking in aSustainable Living Lab, its associated knowledge generation and application, and how different stages of UrbanDesign Thinking contribute to the potential of Sustainable Living Labs to accelerate urban sustainability tran-sitions via S.PSSs. Therefore, the author analyzed empirical data from a series of in‐depth interviews and written surveys and was actively involved within a cycling Sustainable Living Lab in Berlin, Germany.
Keywords: Nachhaltige Stadtentwicklung; Reallabor; Methodenanwendung; Lieferverkehr; Stadtverkehr; Stadtlogistik; Design Thinking